2003
DOI: 10.1021/la034868p
|View full text |Cite
|
Sign up to set email alerts
|

Protein Exposed Hydrophobicity Reduces the Kinetic Barrier for Adsorption of Ovalbumin to the Air−Water Interface

Abstract: Using native and caprylated ovalbumin, the role of exposed hydrophobicity on the kinetics of protein adsorption to the air-water interface is studied. First, changes in the chemical properties of the protein upon caprylation were characterized followed by measurement of the changes in adsorption kinetics. No change in the molecular structure of ovalbumin was observed upon caprylation. However, aggregation of the protein was observed when more than three capryl chains were coupled per protein. A batch of capryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 35 publications
3
100
2
Order By: Relevance
“…This effect is further amplified by the finding that local protein concentrations at the air-water interface can reach up to 150 to 300 mg/ml (Meinders et al, 2001). The rate of absorption to the air-water interface has been reported to depend largely on the hydrophobic nature of the protein under investigation (Kudryashova et al, 2003;Wierenga et al, 2003). Increasing the exposed hydrophobicity of proteins by means of conjugation with lipid chains was shown to increase the adsorption rate to the air-water interface .…”
Section: Foamsmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is further amplified by the finding that local protein concentrations at the air-water interface can reach up to 150 to 300 mg/ml (Meinders et al, 2001). The rate of absorption to the air-water interface has been reported to depend largely on the hydrophobic nature of the protein under investigation (Kudryashova et al, 2003;Wierenga et al, 2003). Increasing the exposed hydrophobicity of proteins by means of conjugation with lipid chains was shown to increase the adsorption rate to the air-water interface .…”
Section: Foamsmentioning
confidence: 99%
“…Increased exposed hydrophobicity of proteins has for example been related to an improved capacity to form and stabilize emulsions and foams which is the result of improved potential to interact with hydrophobic surfaces, both the air-water and oil-water interface, and including (model)membranes (Nakai, 1983;Wierenga et al, 2003;reviewed in Wilde, 2000;Wilde et al, 2004). Various saturated and unsaturated fatty acids have been employed to induce lipophilization of proteins including caproic acid (Liu et al, 2000), capric acid (Aewsiri et al, 2010;Liu et al, 2000), lauric acid (Aewsiri et al, 2010), myristic acid (Aewsiri et al, 2010;Ibrahim et al, 1993;Liu et al, 2000), palmitic acid (Haque et al, 1982;Haque & Kito, 1983a, 1983bIbrahim et al, 1991), stearic acid (Djagny et al, 2001;Ibrahim et al, 1993), and oxidized forms of linoleic acid (Aewsiri et al, 2011a(Aewsiri et al, , 2011b, and the efficiency of the lipophilization reaction was found to be inversely proportional to the length of the lipid chains used (Liu et al, 2000).…”
Section: Lipophilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for kale it was shown that the protein yield (g/m 2 ) increased from 11.5 to 26.2% when a combination of nitrogen-phosphorus-potassium (NPK) fertilizer was used (4,36). At the same time the ratio of protein nitrogen to total nitrogen in the extracted juice increased from 64.6 to 67.7%.…”
Section: Agronomic and Environmental Factors Affecting Quantity And Qmentioning
confidence: 99%
“…At the same time the ratio of protein nitrogen to total nitrogen in the extracted juice increased from 64.6 to 67.7%. Critical parameters regarding fertilization are the type and amount of fertilizer and the application time (36). Weather conditions during plant growth also play a key role in the amount of extractable leaf proteins.…”
Section: Agronomic and Environmental Factors Affecting Quantity And Qmentioning
confidence: 99%